2018
DOI: 10.1097/wnr.0000000000001007
|View full text |Cite
|
Sign up to set email alerts
|

A novel online fluorescence method for in-vivo measurement of hydrogen peroxide during oxidative stress produced in a temporal lobe epilepsy model

Abstract: Status epilepticus (SE) can result in an overproduction of hydrogen peroxide (H2O2), which contributes to oxidative stress and brain injury during different phases of epileptogenesis and seizures. In this study, we measured the extracellular H2O2 concentration in the rat hippocampus in a temporal lobe epilepsy model. A new fluorescent technique for measuring H2O2 in vivo simultaneously with electroencephalography recording was tested. The method consists of mixing microdialysate with an enzymatic reactor to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We continue to use H 2 O 2 to simulate ROS and stimulate the nanogel to investigate its ROS responsiveness and drug release properties . It has been reported that the highest concentration of extracellular H 2 O 2 in epileptic foci can be close to 50 μmol/L, so we choose 50 μmol/L H 2 O 2 to stimulate the nanogel . We find that the DLS particle size and PDI of our nanogel become larger and larger over time (Figure A).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…We continue to use H 2 O 2 to simulate ROS and stimulate the nanogel to investigate its ROS responsiveness and drug release properties . It has been reported that the highest concentration of extracellular H 2 O 2 in epileptic foci can be close to 50 μmol/L, so we choose 50 μmol/L H 2 O 2 to stimulate the nanogel . We find that the DLS particle size and PDI of our nanogel become larger and larger over time (Figure A).…”
Section: Resultsmentioning
confidence: 98%
“…We continue to use H 2 O 2 to simulate ROS and stimulate the nanogel to investigate its ROS responsiveness and drug release properties. 65 20 We find that the DLS particle size and PDI of our nanogel become larger and larger over time (Figure 2A).…”
Section: In Vitro Characterization Of Ros/electromentioning
confidence: 83%
See 2 more Smart Citations
“…In a TLE model, it was demonstrated that H 2 O 2 was released during SE and correlated with changes in electrical activity. The increase in H 2 O 2 levels was observed after 15 days of SE, and this increase persisted during the chronic period, indicating that this reactive species could participate in the generation and maintenance of seizures [ 60 ]. Another study detected an increase in 8-OHdG in mitochondria isolated from the hippocampus of rats with TLE immediately after SE.…”
Section: Discussionmentioning
confidence: 99%